Hubungan Antara Perilaku Merokok Dengan Tingkat Kepercayaan Diri Pada Remaja Putra Usia 16 Tahun Di Kota Malang - Nisa' Ailmi Lidya Artha Revica (PROFESSIONAL HEALTH JOURNAL, 2023)
ABSTRACT Introduction: Smoking behavior is an carried activity with smoke inhaling and then put out trough the mouth. In the adolescent group, smoking behavior will also affect psychosocial development including confidence. This study aims to determine the relationship between smoking behavior and the levels of confidence in the boys adolescents age 16 years at Malang city. Method: Quantitative research using design cross sectional. The population is boys adolescents age 16 years as a smoker 250 respondents. Sampling with simple random sampling technique, obtained a samples of 154 respondents. The instrument used is questionare. Data analysis using Spearman Rank statistics. Result: Based on the results of the analysis of 154 respondents, students with low smoking behavior as much as 78 (50,6%), medium 53 (34,4%), high 23 (15%). Respondents with level of low self confidence as much 101 (65,6%) and then high level of self confidence 53 (34,4%). Conclusion: From the analysis results obtained significant results p = 0,000 where the value of p < a (0,000 < 0,05), which means there a relationship between smoking behavior with the level of confidence in boys age 16 years with a correlation value of 0,433 and the direction of a positive relationship that is the lower the smoking behavior followed by the level of self confidence. However, there are some variables which haven’t been explored related to self confidence. It is expected that parents can provide better direction and guidance to adolescents to be more optimal. ABSTRAK Latar belakang : Perilaku merokok adalah kegiatan yang dilakukan dengan cara menghirup asap dan mengeluarkan kembali melalui mulut. Pada kelompok remaja, perilaku merokok akan berpengaruh terhadap perkembangan psikososial termasuk kepercayaan diri. Penelitian ini bertujuan untuk mengetahui hubungan antara perilaku merokok dengan tingkat kepercayaan diri pada remaja putra usia 16 tahun di kota Malang. Metode: Penelitian kuantitatif yang menggunakan desain Cross Sectional. Populasinya adalah remaja putra usia 16 tahun sebagai perokok sebanyak 250 responden. Pengambilan sampel dengan teknik Simple Random Sampling, didapatkan sampel sebanyak 154 responden. Instrumen yang digunakan adalah kuesioner. Analisis data menggunakan uji statistik Spearman Rank. Hasil: Berdasarkan hasil analisis dari 154 responden, siswa dengan perilaku merokok rendah sebanyak 78 (50,6%), sedang 53 (34,4%), tinggi 23 (15%). Responden dengan tingkat kepercayaan diri rendah sebanyak 101 (65,6%) dan kepercayaan diri tinggi 53 (34,4%). Kesimpulan : Dari hasil analisis didapatkan hasil yang signifikan p = 0,000 dimana nilai p < α (0,000<0,05) yang artinya ada hubungan antara perilaku merokok dengan tingkat kepercayaan diri pada remaja putra usia 16 tahun dengan nilai korelasi sebesar 0,433 dan arah hubungan positif yaitu semakin rendah perilaku merokok diikuti dengan tingkat kepercayaan diri rendah. Akan tetapi ada beberapa variabel yang belum dieksplorasi terkait dengan kepercayaan diri. Diharapkan orang tua dapat memberikan arahan dan bimbingan yang lebih baik pada remaja agar lebih optimal.